HIV-positive and HHV-8-negative primary effusion lymphoma complicated with coronary heart disease: a Case Report and literature review - Zhang, Wei; Zhang, Ying; Yuan, Jing (Frontiers in Medicine, 2025)
ObjectiveThis case report describes a rare instance of human immunodeficiency virus (HIV)-positive, human herpesvirus-8 (HHV-8)-negative, and Epstein-Barr virus (EBV)-negative primary effusion lymphoma (PEL) associated with pulmonary effusions likely caused by congestive heart failure (CHF). The new classification added in the fifth edition of the World Health Organization’s lymphoma classification is named “Fluid Overload-Associated Large B-Cell Lymphoma.”MethodsThe diagnosis and treatment of a 71-years-old male patient with acquired immune deficiency syndrome (AIDS) and PEL admitted to the Department of Infectious Diseases in Chongqing Public Health Medical Center in March 2022 were detailed, and relevant literature was reviewed.ResultsThe patient had been receiving antiretroviral therapy (ART) with lamivudine (3TC) + tenofovir (TDF) + efavirenz (EFV) for 17 years. The primary clinical manifestations were large pericardial and pleural effusions. Pathological examination confirmed HHV-8 and EBV-negative large B-cell lymphoma. The effusions were drained effectively, and the patient received ART and two cycles of R-CDOP chemotherapy. Atrial fibrillation and coronary heart disease (CHD) were diagnosed during the course of the disease. After 2 years of follow-up, no recurrence of symptoms was observed.ConclusionThis case highlights the importance of recognizing rare HHV-8 negative PELs and the need to monitor underlying conditions such as CHD that may contribute to effusion formation. It underscores the diagnostic challenges and the necessity of a multidisciplinary approach in managing such cases.